DESIGN OF CENTRALIZED WASTEWATER SEWERAGE SYSTEM IN SMALL LENGKANG ISLAND, BATAM CITY, INDONESIA - Yosef Adicita; I Wayan Koko Suryawan; Muhammad Rizki Apritama (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2020)
One of the small islands within the Indonesia-Singapore border is Lengkang Island. Wastewater collection infrastructure services on Lengkang Island need to be assessed to improve Sustainable Development Goals (SDGs), where access to wastewater services must reach 100%. The purpose of this study is to determine the existing conditions of wastewater management and to plan a centralized wastewater sewerage system on Lengkang Island involving the community. The existing condition shows that all residents channel wastewater into the sea. Only a few houses have toilets, semi-permanent houses on land. Non-permanent houses built on the sea do not have latrines, where stools are dumped directly into the sea. Tripikon-S is one way to overcome the problem of impermanent homes that do not have latrines. Latrine does not provide a solution to the effects of eutropication. Centralized wastewater collection system and wastewater treatment is one way to overcome this. The results of the planning of wastewater collection systems using PVC pipes mentioned the pipe diameter between 32 mm - 60 mm, with a speed of 0.3 m/sec -1.31 m/sec. With this centralized wastewater sewerage system infrastructure, community participation is expected to increase environmentally friendly development.